2013
DOI: 10.1002/bse.1769
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in the Transport and Logistics Sector: Lacking Environmental Measures

Abstract: Sustainability as part of the development of companies' business strategies is gaining in importance. Due to its impact on the environment, this is particularly essential for companies of the transport and logistics sector. This paper explores several factors that influence the environmental behaviour of transport and logistics companies in Austria. It discusses the importance of the economic impact on environmental management decision in detail and analyses the sector's specific characteristics in terms of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 48 publications
1
80
0
1
Order By: Relevance
“…Impact of green actions on 3PLs' performance [3,38,40,41,56,61,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80].…”
Section: Content Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Impact of green actions on 3PLs' performance [3,38,40,41,56,61,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80].…”
Section: Content Analysismentioning
confidence: 99%
“…The importance for 3PLs to be energy efficient in transportation has been found by a number of other papers. Oberhofer and Dieplinger (2014) [3] found that energy-efficient vehicles is one of the most used measures in the sample of logistics companies they analyzed in Austria. Similarly, the findings of Evangelista (2014) [25] showed that energy efficiency measures were used by the Italian 3PL companies having a higher level of green concern.…”
Section: Green Actions and The Impact On 3pls' Performancementioning
confidence: 99%
See 3 more Smart Citations